2022
DOI: 10.1145/3487606
|View full text |Cite
|
Sign up to set email alerts
|

INC-Hg: An Intelligent Collaborative Haptic-Gripper Virtual Reality System

Abstract: Collaborative Virtual Environments (CVE) have shown potential to be an effective social skill training platform for children with Autism Spectrum Disorders (ASD) to learn and practice collaborative and communication skills through peer interactions. However, most existing CVE systems require that appropriately matched partners be available at the same time to promote interaction, which limits their applicability to some community settings due to scheduling constraints. A second shortcoming of these more natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
6
0
2
Order By: Relevance
“…The haptic device was the least favorite device compared to the other devices, which indicated that ease of use was more important to the participants than immersive interaction since participants were least familiar with the use of the haptic device. Existing studies that explored the use of haptic devices in VR-based interactions have shown that with practice, haptic devices can be well accepted by participants [23], [28]. Therefore, for future studies involving teamwork skills training, we will use either the gamepad or keyboard and mouse, while haptic device could be used in studies that examine fine motor skills training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The haptic device was the least favorite device compared to the other devices, which indicated that ease of use was more important to the participants than immersive interaction since participants were least familiar with the use of the haptic device. Existing studies that explored the use of haptic devices in VR-based interactions have shown that with practice, haptic devices can be well accepted by participants [23], [28]. Therefore, for future studies involving teamwork skills training, we will use either the gamepad or keyboard and mouse, while haptic device could be used in studies that examine fine motor skills training.…”
Section: Discussionmentioning
confidence: 99%
“…Effective teamwork requires collaboration among individuals working together, making collaboration an important indicator of teamwork performance [27]. A collaborative virtual environment (CVE) extends the benefits of conventional VR technology by supporting multi-user interaction within the shared virtual space, allowing users to naturally communicate with each other [28], potentially increasing generalizability of learned skills to the real world. Several recent CVE-based interactions have been promising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habilidades motoras finas são habilidades que exigem o uso dos músculos para pequenas ac ¸ões como agarrar, manipular e alcanc ¸ar objetos [Arshad et al 2020]. A partir disso, pesquisas na literatura indicam que o uso de jogos digitais impacta positivamente as habilidades motoras finas de crianc ¸as com TEA ao estimular melhorias significativas no desempenho de tarefas individuais e colaborativas e ao promover a comunicac ¸ão social e a colaborac ¸ão [Zhao et al 2021].…”
Section: Introduc ¸ãOunclassified
“…Visando apoiar os processos terapêuticos, foram identificadas tecnologias na literatura que usam de jogos e AVs 3D para treinamento de habilidades motoras, além da colaborac ¸ão e a comunicac ¸ão, com foco em crianc ¸as com TEA [Zhao et al 2021], [Giraud et al 2021], [Amat et al 2021]. Tarefas motoras finas na forma de jogos de computador podem proporcionar recompensas ou consequências consistentes e em tempo real para as respostas, o que pode incentivar o envolvimento e reter a atenc ¸ão das crianc ¸as [Zhao et al 2018].…”
Section: Introduc ¸ãOunclassified